The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1002/imhj.21400
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Positive Mother–Infant Relationships: A Randomized Trial of Community Doula Support For Young Mothers

Abstract: Doulas, whose traditional role is to support women during labor and delivery, are being increasingly utilized within community-based programs where a primary goal is supporting mother-infant relationships. The present study investigated the effect of doula services on parenting among young, low-income mothers. A total of 248 pregnant women were randomly assigned to receive either doula services or routine medical and social services. The doulas provided prenatal home visitation, support during labor and delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 65 publications
0
57
0
Order By: Relevance
“…The model has been described in a variety of sources, including a book (Abramson, Isaacs, & Breedlove, ) and a documentary film (Alpert & Suffredin, ). Randomized controlled trials of the community doula model have shown positive impacts of the intervention on breast‐feeding as well as early mother–infant interaction (Edwards et al., ; Hans, Edwards, & Zhang, ; Hans et al., ).…”
Section: Reproductive Justice Within Two Infant Mental Health Programsmentioning
confidence: 99%
“…The model has been described in a variety of sources, including a book (Abramson, Isaacs, & Breedlove, ) and a documentary film (Alpert & Suffredin, ). Randomized controlled trials of the community doula model have shown positive impacts of the intervention on breast‐feeding as well as early mother–infant interaction (Edwards et al., ; Hans, Edwards, & Zhang, ; Hans et al., ).…”
Section: Reproductive Justice Within Two Infant Mental Health Programsmentioning
confidence: 99%
“…Although the IRB and hospital HIPAA advisors did not allow collection of demographic or health information on non-participants, these women were almost certainly African American and low-income given the population served by the clinics. At the end of the prenatal interview, mothers were assigned to receive either community-based doula services (n = 124), or regular prenatal medical and social services (n = 124) [44].…”
Section: Participantsmentioning
confidence: 99%
“…Kozhimannil et al (2013) concluded that the emotional support provided by "Doula" can relieve the labor pain, increase the satisfaction, and create a pleasant experience and positive outcome (42,43). Doula is an experienced woman who provides continuous emotional support to women during childbirth (30,(43)(44)(45). Moreover, Boryri et al (2016) stated that ongoing support from Doula or one of the family members reduced the medical interventions, increased the mother's satisfaction, enhanced the neonatal outcomes, and 13 improved the psychological wellbeing of mothers(4).…”
Section: Discussionmentioning
confidence: 99%